2014
DOI: 10.1080/01932691.2013.792272
|View full text |Cite
|
Sign up to set email alerts
|

Foam Flooding with Ultra-Low Interfacial Tension to Enhance Heavy Oil Recovery

Abstract: Severe viscous fingering during water flooding of heavy oil leaves a large amount of oil untouched in the reservoir. Improving sweep efficiency is vital for increasing heavy oil recovery. Previous researches have proved that foam flooding can increase the sweep efficiency and oil recovery. The polymers could make the foam more stable and have better plugging capacity, but the interfacial tension (IFT) of oil and water increase which could decrease the displacement efficiency of the heavy oil. In view of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This demonstrates that polymer can greatly improve the foam stability, which is mainly related to the stability of foam film. Such a film should have slow liquid drainage and good elasticity to stand some deformation without rupturing. , The polymer can enhance the viscosity of the foaming solution (that is, the liquid solution within the foam lamella), reduce the rate of liquid drainage in the foam film, and create a protective viscoelastic film around the gas bubble, and consequently improve the foam stability. However, the addition of polymer also adversely influences foaming ability as shown in Figure .…”
Section: Experimental Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This demonstrates that polymer can greatly improve the foam stability, which is mainly related to the stability of foam film. Such a film should have slow liquid drainage and good elasticity to stand some deformation without rupturing. , The polymer can enhance the viscosity of the foaming solution (that is, the liquid solution within the foam lamella), reduce the rate of liquid drainage in the foam film, and create a protective viscoelastic film around the gas bubble, and consequently improve the foam stability. However, the addition of polymer also adversely influences foaming ability as shown in Figure .…”
Section: Experimental Results and Discussionmentioning
confidence: 99%
“…36 Kang et al and Zhang et al explored a novel method of ultralow interfacial tension PEF for a heavy oil (461 mPa•s at 60 °C) and discovered that this new method could greatly enhance oil production and control water cut and direct injection foam had a better performance compared to N 2 /water coinjection and water alternating gas. 37,38 Telmadarreie and Trivedi studied PEF flooding for improving postsurfactant flooding in oil-wet fractured carbonate reservoirs, and their micromodel tests showed that PEF could enhance sweep efficiency by diverting surfactant liquid from the fractures into the matrix. 39 They also compared the performance of foam and PEF using a heavy oil (670 mPa•s at 22 °C) in both homogeneous and fractured rock samples and found that PEF had better performance than foam, with more stable frontal displacement, better sweep efficiency, and higher trapped gas saturation in the cores, and that PEF significantly improved heavy oil recovery in the fractured cores by the liquid diversion into the matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactant flooding is a promising EOR technique employed by the production sector since 1970s decade 5,6 . This type of recovery functions by allowing surfactants or “surface‐active agents” to adsorb onto the interface of oil/water, thereby decreasing interfacial free energy and increasing dimensionless capillary number 5‐7 . Polymer improves the viscosity of displacing (injected) fluid to reduce the mobility ratio between water and oil 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant flooding is a promising EOR technique employed by the production sector since 1970s decade [5,6]. This type of oil recovery functions by allowing surfactants or "surface-active agents" to adsorb onto the interface of oil/water, thereby decreasing interfacial free energy and increasing dimensionless capillary number [5][6][7]. Polymer improves the viscosity of displacing (injected) fluid to reduce the mobility ratio between water and oil [8,9].…”
Section: Introductionmentioning
confidence: 99%